Optimum Utilization of Volcanic Rock as Pozzolana for the Maximum Compressive Strength of Mortar - Zeeshan Ahmad; Muhammad Suleman; Masooma Sabtain; Muhammad Abdur Rehman Hamid; Waqas ur Rahman; Hamid Bilal (Journal of ICT, Design, Engineering and Technological Science, 2023)
This research describes the Dir-Utror volcanics in terms of geochemical analysis and compressive strength results to determine their Pozzolanic properties. Adding pozzolana to cement mortar enhances compressive strength by providing a supplementary binding material that reacts with calcium hydroxide to form additional cementitious compounds. This not only improves the overall durability of the mortar but also reduces the risk of cracks, making it an economically viable solution for constructing robust and long-lasting structures. For this purpose, this research concentrates on exploring the Pozzolanic characteristics using the X-ray Florescence technique, to illustrate chemical composition, and compressive strength test using 2 inch or 50 mm mortar cube. According to chemical composition and compressive strength results and by comparing it with the standard cube compression results with Ordinary Portland Cement (OPC), these materials are suitable to use as an additive or substitute for cement replacement. Four different samples were collected from the same region three of them, at 28 days of age, gave satisfactory results, while a single sample (sample 2) had less compression result than the standard cubes, cured for 28 days, according to the graphs’ trend lines. A total of 78 (2-inch) cubes were made, 6 considered to be standard (OPC) and 72 for 4 different samples. Three cubes for each ratio, such as by 15%, 25 and 35%, have been prepared and have taken the average value for each Pozzolan-ratio sample. The 1st series, 36 Pozzolan cubes’, compressive strength results were conducted after 14 days of age which was not as satisfactory as the 2nd series cured for 28 days of age.